Active and stable hydrotalcite derived Ni catalysts for CO2 reforming of methane: Comparison with catalysts by incipient wetness. (May 2018) - Kalai, Dori Yosef; Stangeland, Kristian; Jin, Yiying; Yu, Zhixin
Graphical abstract: Highlights: HT-derived Ni catalysts are superior to catalysts prepared by incipient wetness. Pure HT structure is essential to obtain Ni catalysts with higher DRM performance. Higher temperatures are preferred for enhanced activity and stability in DRM. Pure HT-derived Ni catalyst is effective for direct biogas upgrading. Abstract: Dry reforming of methane (DRM) for synthesis gas production has a promising future in technological developments due to the utilization of CO2, the principal anthropogenic greenhouse gas. However, this process is still far from industrialization because of catalyst deactivation by coking and sintering. In this study, a series of Ni(Mg)-Al hydrotalcite (HT) derived catalysts were prepared and compared to catalysts prepared by the conventional incipient wetness method. The as-prepared and calcined catalysts were characterized by N2 adsorption-desorption, X-ray diffraction, temperature programmed reduction, H2 -chemisorption and scanning electron microscope. DRM experiments were carried out at a very high gas hourly space velocity of 240, 000 ml/ (gcat  h) to compare the activity and stability of the catalysts. The 20Ni-Mg-Al HT showed remarkably high and stable conversions in DRM at 750 °C, while the 12Ni-Al HT catalyst presented the poorest activity, resulting from impure HT structure and consequently unstable Ni particles. The 20Ni-Mg-Al HT was further proved to be active and stable under various biogas compositions, even in the deficiency of CO2 . This study demonstrates that pure HT-derived Ni catalysts are superior for DRM at different reaction conditions, and can be utilized for direct biogas upgrading.